Radon Activity Concentration Measurements in the Water Collected from the Lower Zab River in the Kurdistan Region of Iraq - Smail, Jahfer M.; Azeez, Hiwa H.; Mansour, Habeeb H.; Ahmad, Saddon T. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
This study aims to assess radon levels in the water of the Lower Zab River. Knowing the radon concentrations is crucial for understanding the potential risks to human health and implementing protective measures. ARAD7-H2O detector has been used to measure the radon concentration in 28 water samples from the Lower Zab River in the Kurdistan Region of Iraq. Results show that the radon activity concentrations ranged from 0.5 to 4 Bq.L−1, with an average of 0.61 Bq.L−1, and the resulting annual effective dose (AED) varied from 0.137 to 60.06 Sv.y−1, with an average of 12.08 Sv.y−1. The average radon concentration and AED in the measured samples are below the reference levels recommended by the ICRP and the World Health Organization. Consequently, the LZR water is suitable for human consumption and use and does not present any health hazards related to radon exposure.